PENGARUH NON PERFORMING LOAN (NPL) ATAU KREDIT MACET DAN PROFITABILITAS TERHADAP TINGKAT KERUGIAN PADA PERUSAHAAN PT. ULTRA ELEKTRONIK NUSANTARA - Maeliany; Maharani, Yunita; Novika (Jurnal Akuntansi Bisnis Dan Keuangan, 2024)
The research results show that through partial testing, Non-Performing Loans (NPL) or bad loans have a positive and significant effect on the level of losses with a significance value of 0.017 < 0.05 and a t-value of 3.800 > t-table value of 1.894. Profitability (ROA) has a positive and significant effect on the level of losses with a significance value of 0.030 < 0.05 and a t-value of 2.223 > t-table value of 1.894. Profitability (ROE) has a positive and significant effect on the level of losses with a significance value of 0.021 < 0.05 and a t-value of 2.386 > t-table value of 1.894. Profitability (ROI) has a positive and significant effect on the level of losses with a significance value of 0.036 < 0.05 and a t-value of 2.166 > t-table value of 1.894. The simultaneous test results show that Non-Performing Loans (NPL) or bad loans and Profitability (ROA, ROE, ROI) have a positive and significant effect on the level of losses with a significance value of 0.0045 < 0.05 and an f-value of 6.334 > f-table value of 4.12. Based on the results of the analysis and data processing, it can be concluded that both theoretically and from field data, Non-Performing Loans (NPL) or bad loans and Profitability (ROA, ROE, ROI) have a significant effect on the level of losses at PT. UEN for the period January – December 2023.